2015
DOI: 10.1073/pnas.1419388112
|View full text |Cite
|
Sign up to set email alerts
|

MinD-like ATPase FlhG effects location and number of bacterial flagella during C-ring assembly

Abstract: The number and location of flagella, bacterial organelles of locomotion, are species specific and appear in regular patterns that represent one of the earliest taxonomic criteria in microbiology. However, the mechanisms that reproducibly establish these patterns during each round of cell division are poorly understood. FlhG (previously YlxH) is a major determinant for a variety of flagellation patterns. Here, we show that FlhG is a structural homolog of the ATPase MinD, which serves in cell-division site deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
146
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(148 citation statements)
references
References 49 publications
2
146
0
Order By: Relevance
“…Our present results suggest a potential interaction between FlrA and FlhG to control the transcription of the bpfA operon; however, we still cannot exclude the possibility that other mechanisms may be involved. It has been reported that FlhG affects the number and location of flagella not as a result of FlrA but through direct interaction with flagellar C-ring proteins (38).…”
Section: Discussionmentioning
confidence: 99%
“…Our present results suggest a potential interaction between FlrA and FlhG to control the transcription of the bpfA operon; however, we still cannot exclude the possibility that other mechanisms may be involved. It has been reported that FlhG affects the number and location of flagella not as a result of FlrA but through direct interaction with flagellar C-ring proteins (38).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were produced in BL21 (DE3) (Novagen). After cell lysis by a Microfluidizer (M110-L, Microfluidics), cell debris was removed by high-speed centrifugation and proteins were purified by Ni-ion affinity-and size-exclusion chromatography, as described recently (43). The SEC buffer consisted of 20 mM Hepes-Na (pH 7.5), 200 mM NaCl, 20 mM KCl, and 20 mM MgCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…FleQ works in concert with another protein, FleN, which is an ATPase with a deviant Walker A motif (24,25). FleN is required for full expression of biofilm-related genes in the presence of c-di-GMP (4), but its exact biological role in biofilm gene expression is not clear.…”
Section: Figmentioning
confidence: 99%